Cuba and the question of human rights: From media representation to factual reality - Salim Lamrani (Études Caribéennes)
Since 1959 and the advent of the Cuban Revolution, and especially since 1991 and the fall of the Soviet Union, Cuba has been invariably indicted on the issue of human rights. There is widespread public consensus, especially in the West, that associates the island with human rights violations. Without seeking to deny the possible violations of fundamental rights that may occur in Cuban society, it is appropriate to ask whether there is a correlation between the extent of the violations of human rights identified by international institutions in a particular country and the media exposure it receives. To answer this question, this article proposes a comparative study, based on Amnesty International’s latest annual report, of four countries: Cuba, the United States, France and Spain.Desde 1959 y el advenimiento de la Revolución Cubana, y más particularmente desde 1991 y la caída de la Unión Soviética, Cuba resulta invariablemente acusada sobre la cuestión de los derechos humanos. Existe un consenso ampliamente difundido en el seno de la opinión pública, particularmente en Occidente, para asociar la isla a violaciones de los derechos humanos. Sin buscar negar los eventuales atentados a los derechos fundamentales que pueden ocurrir en el seno de la sociedad cubana, conviene preguntarse si hay una correlación entre la importancia de las violaciones de los derechos humanos observadas por las instituciones internacionales y la exposición mediática que se le otorga. Para responder a esta interrogante, este trabajo propone realizar un estudio comparativo, basado en el último informe anual de Amnistía Internacional, entre cuatro países: Cuba, Estados Unidos, Francia y España.